Advances in surface modification and functionalization for tailoring the characteristics of thin films and membranes via chemical vapor deposition techniques. Issue 15 (23rd February 2023) - Mostafavi, Amir Hossein; Mishra, Ajay Kumar; Gallucci, Fausto; Kim, Jong Hak; Ulbricht, Mathias; Coclite, Anna Maria; Hosseini, Seyed Saeid
Abstract: Advanced materials are among the prime drivers for technological revolutions and transformation in quality of lives. Over time, several modification techniques have emerged enabling development of novel materials with extraordinary features. The present review aims to introduce various promising chemical and physical surface modification techniques instrumental for tailoring the characteristics of thin films and membranes. Meticulous discussions are provided over chemical vapor deposition (CVD) techniques evolved for addressing the demands for materials with desired functionalities. Also, essential criteria for the selection of substrates, modifying and precursor materials for an effective CVD modification are elaborated. Investigations are extended to unraveling the role of various process parameters on the quality and properties of deposition. Special attention is paid to the significance and performance of CVD‐based membranes and thin films for industrial applications ranging from desalination and water treatment to energy and environment, biomedical and life science as well as packaging. The goal has been to establish a scientific platform for a timely tracking of the prevailing trends in exploitation of CVD techniques and highlighting the unexplored opportunities. This also helps in identification of the scientific and technical gaps and setting directions for further progress in the fields of thin films and membranes. Abstract : Prominent applications of chemical vapor deposition techniques for surface modification and functionalization of thin films and membranes.